The Victim's Condition in Criminal Persecution: Sociological and legal aspects - Lanna, Letícia Marques (2020)
The present article initially seeks to make a historical analysis of the theme seeking to analyze, according to the chronological and historical moment, the role of the victim in criminal action. Afterwards, the analysis of the victim's participation in the pre-procedural phase and in the criminal procedural phase is carried out according to the type of action taken. In continuation, there is a chronological approach to legislative procedural innovations in a chronological way, where it seeks to analyze with emphasis the advances regarding the protection of the victim's rights and the performance of the victim not only as a means of evidence but as a procedural subject, furthermore, it aims to analyze the current trend of Criminal Law for Consensual Justice that prioritizes the transaction and the agreement between victim and offender. At the end, a critical approach is carried out, analyzing the role of the State as a direct victim and the supremacy of the interest of public bodies in the face of the interest of the victim whose right has been injured, which should be given priority in the state jus puniendi. article is to analyze the role of the victim in criminal prosecution, analyzing the advances according to the emergence of laws, the most active role that the same has assumed despite there being great obstacles analyzing the disparity between what is instituted in law and what occurs in the situation concrete. Currently, legislative innovations have emerged that have prioritized the victim's interest in criminal prosecution and with regard to the punishment of the agent